2016
DOI: 10.1186/s12903-016-0218-8
|View full text |Cite
|
Sign up to set email alerts
|

Sympathomimetic effects of chronic methamphetamine abuse on oral health: a cross-sectional study

Abstract: BackgroundMethamphetamine, a highly addictive sympathomimetic stimulant, is currently widely abused worldwide and has been associated with devastating effects on oral health, resulting in the term “meth mouth”. However, “meth mouth” pathology is primarily based on case reports with a lack of systematic clinical evaluation. Therefore, we have conducted a systematic study to investigate (1) the pharmacological impact of methamphetamine on oral health with regard to saliva function, including the parameters saliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 11 publications
(19 reference statements)
0
38
0
3
Order By: Relevance
“…The illicit drugs can stimulate α-adrenergic receptors within the salivary gland vasculature, causing vasoconstriction and reduction of salivary flow (hyposalivation), which greatly weakens protective properties such as the neutralization of plaque-induced acids and the remineralization of dental enamel [ 24 ]. Repetitive meth abuse can also lead to a decrease in salivary pH [ 25 ], which elevates the risk for dental erosion. In addition, Tipton DA found that meth can significantly increase bacterial lipopolysaccharide (LPS)-stimulated IL-1β levels secreted by monocyte/macrophages, which could contribute to periodontitis in meth abusers [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The illicit drugs can stimulate α-adrenergic receptors within the salivary gland vasculature, causing vasoconstriction and reduction of salivary flow (hyposalivation), which greatly weakens protective properties such as the neutralization of plaque-induced acids and the remineralization of dental enamel [ 24 ]. Repetitive meth abuse can also lead to a decrease in salivary pH [ 25 ], which elevates the risk for dental erosion. In addition, Tipton DA found that meth can significantly increase bacterial lipopolysaccharide (LPS)-stimulated IL-1β levels secreted by monocyte/macrophages, which could contribute to periodontitis in meth abusers [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 18 included studies, 12 were cross-sectional studies, 14,15,16,18,19,20,22,24,25,26,27 4 were cohort studies, 11,12,13,17 and 2 were casecontrol studies. 21,23 The total samples from all included studies were 10389, which 4449 were male and 3868 were female. 6 studies did not specify the gender of the samples.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of included studies were recorded on table 1. The most frequent psychotropic drugs used were methamphetamine (MA) (50%) 12,13,14,18,19,20,21,26,27 , cocaine (44%) 12,17,18,22,23,25,26,28 , heroin (38%) 12,14,15,16,17,18,27 , cannabis (38%) 11,12,17,18,22,27 , opium (11%) 24,27 . 6 studies were using polydrug abusers as samples.…”
Section: Resultsmentioning
confidence: 99%
“…The consumption of methamphetamines is rapidly increasing on a worldwide scale and, therefore, its forensic relevance. Several gastrointestinal microorganisms, such as species belonging to the genera Enterobacterium, Enterococcus, Lactobacillus, Clostridium and Bacterioides, are responsible for the N-demethylation of methamphetamines converting these compounds into amphetamines (Castle et al 2017;Rommel et al 2016).…”
Section: Toxicologymentioning
confidence: 99%